The effectiveness and safety of repetitive transcranial magnetic stimulation on spasticity after upper motor neuron injury: A systematic review and meta-analysis - Fan, Jin; Fu, Hui; Xie, Xiaolong; Zhong, Dongling; Li, Yuxi; Liu, Xiaobo; Zhang, Huiling; Zhang, Jun; Huang, Jiaxi; Li, Juan; Jin, Rongjiang; Zheng, Zhong (Frontiers in Neural Circuits, 2022)
To systematically evaluate the effectiveness and safety of repetitive transcranial magnetic stimulation (rTMS) on spasticity after upper motor neuron (UMN) injury. Eight electronic databases were searched from inception to August 6th, 2022. Randomized controlled trials (RCTs) investigating the effectiveness and safety of rTMS on spasticity after UMN injury were retrieved. Two reviewers independently screened studies, extracted data, and assessed the risk of bias. Review Manager 5.3 and Stata 14.0 software were used to synthesize data. The certainty of the evidence was appraised with the Grade of Recommendation, Assessment, Development and Evaluation tool. Forty-two studies with a total of 2108 patients were included. The results of meta-analysis revealed that, compared with control group, rTMS could significantly decrease scores of the Modified Ashworth Scale (MAS) in patients with UMN injury. The subgroup analysis discovered that rTMS effectively decreased the MAS scores in patients with stroke. Meanwhile, rTMS treatment ＞ ten sessions has better effect and rTMS could decrease the MAS scores of upper limb. Thirty-three patients complained of twitching facial muscles, headache and dizziness, etc. In summary, rTMS could be recommended as an effective and safe therapy to relieve spasticity in patients with UMN injury. However, due to high heterogeneity and limited RCTs, this conclusion should be treated with caution.